2022
DOI: 10.1177/0734242x221122571
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions and actions related to circular fashion items: Perspectives of young Brazilians on circular economy

Abstract: The fashion industry is one of the most important industries for the world economy, but is also one of the most polluting. Some fashion companies have been adopting circular economy initiatives to combat this. Circular fashion (CF) results in cleaner production and reduces textile waste, but depends on consumer collaboration. Several studies analysing consumer CF issues worldwide have been recently published, but these studies are not common in emerging countries. This paper seeks to investigate the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…As De Aguiar Hugo et al. (2023) pointed out in Brazil, waste separation and recycling policies are still very little used by the general population, requiring a change on the part of local governments to encourage selective collection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As De Aguiar Hugo et al. (2023) pointed out in Brazil, waste separation and recycling policies are still very little used by the general population, requiring a change on the part of local governments to encourage selective collection.…”
Section: Resultsmentioning
confidence: 99%
“…De Aguiar Hugo et al. (2023) when analyzing circular fashion identified that young consumers are more concerned about the sustainability of their fashion purchases, as they indicated that they would like to buy fashion items made from green and/or recycled materials produced sustainably. However, most respondents never get involved in circular actions in the fashion chain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The global market size of the TAC industry is around 1.5 trillion USD, and it provides jobs to 300 million people (Papamichael et al, 2023; Platform for Accelerating the Circular Economy, 2021). However, the TAC industry is a highly polluting one due to the excessive use of toxic dyes, water, chemicals and auxiliaries (Camacho-Otero et al, 2020; de Aguiar et al, 2023). Additionally, the popularity of ‘fast fashion’ by leading global fashion brands has compelled the TAC industry to produce more at low cost which led to a decrease in the average number of times a cloth is worn by the user (Ellen MacArthur Foundation, 2017).…”
Section: Introductionmentioning
confidence: 99%